Effects of functional strength training on pain, function, and lower extremity biomechanics in patients with patellofemoral pain syndrome: a randomized clinical trial - Zheyu Xiong; Wei Zheng; Haiwen Wang; Yuan Gao; Chengshuo Wang (Journal of Orthopaedic Surgery and Research)
Abstract Background Patellofemoral pain syndrome (PFPS) is a common disorder affecting the lower extremity. This study aimed to compare the effects of functional strength training (FST) and standard strength training (SST) in PFPS patients. Methods Forty college students (aged 18–30 years) with PFPS and no exercise habits were randomized into FST group (n = 20) and SST group (n = 20). FST group underwent six weeks of lower extremity training focused on functional adaptations, whereas SST group focus on lower extremity strength training. Function (Kujala Patellofemoral Scale, KPS), pain (visual analog scale, VAS), peak joint angles of hip, knee, and ankle, along with muscle activation (step-down test) of Vastus medialis, Vastus lateralis, Biceps femoris, Semitendinosus, Gluteus maximus, and Gluteus medius were assessed at baseline and after intervention. Results FST outperformed SST in pain reduction (p = 0.026) and function (p = 0.006) post-intervention. The FST group also showed increased hip flexion (p < 0.001), gluteus maximus activation (p < 0.001), and reduced knee valgus (p = 0.032), while SST group exhibited greater knee flexion (p = 0.008), and higher activation of the lateral femoral (p < 0.001) and semitendinosus (p < 0.001). Conclusion Interventions focused on functional adaptations result in differential kinematic and muscle activation changes that may result in greater improvements in pain and knee function than lower limb muscle strengthening alone. Trial registration chictr.org.cn. NO: ChiCTR2400087664. Date 01/08/2024.